Pengaruh Pengaruh Model Pembelajaran Think, Pair, Share (TPS) terhadap Kemampuan Menulis Permulaan Siswa Sekolah Dasar: Pengaruh Model Pembelajaran Think, Pair, Share (TPS) terhadap Kemampuan Menulis Permulaan Siswa Sekolah Dasar - safitri, Balqis; Fradana, Ahmad Nurefendi (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2024)
The background this research is the lack of beginningl writing skills of lower grade students. This research aims to determine the effect of the Think, Pair, Share (TPS) learning model on elementary school students beginning writing skills. The TPS model is a model with a conversational design in pairs that is given the opportunity to think, answer and exchange ideas regarding the results obtained. The syntax of the TPS Model is Think, Pair, and Share. In implementing the TPS model of pairing and sharing syntax, educators should provide greater support for students to work together in meetings. With a population of class II students at SDN Lebo, this research used quantitative methods and a "One Group Pretest-Posttest Design" research design. The instrument used in the research was a rubric for students beginning writing skills. From the results of the tests carried out, a significant value (2-Tailed) of 0.000 was obtained from the T-test results, namely a Sig value of 0.000 < 0.05, so H0 was rejected and H1 was accepted. Thus, it can be concluded that being influenced by the TPS learning model has an effect on elementary school students beginning writing skills.